2021
DOI: 10.1002/bab.2181
|View full text |Cite
|
Sign up to set email alerts
|

Production of myo‐inositol: Recent advance and prospective

Abstract: Myo‐inositol and its derivatives have been extensively used in the pharmaceutics, cosmetics, and food and feed industries. In recent years, compared with traditional chemical acid hydrolysis, biological methods have been taken as viable and cost‐effective ways to myo‐inositol production from cheap raw materials. In this review, we provide a thorough overview of the development, progress, current status, and future direction of myo‐inositol production (e.g., chemical acid hydrolysis, microbial fermentation, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Microbial biosynthesis of inositol has been regarded as one of the most promising alternatives to the phytate hydrolysis method. Numerous studies have been reported for metabolic engineering of different strains for inositol production [ 35 ]. To date, E. coli is the most efficient host for inositol biosynthesis, and high inositol production and yield were achieved in this strain [ 14 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Microbial biosynthesis of inositol has been regarded as one of the most promising alternatives to the phytate hydrolysis method. Numerous studies have been reported for metabolic engineering of different strains for inositol production [ 35 ]. To date, E. coli is the most efficient host for inositol biosynthesis, and high inositol production and yield were achieved in this strain [ 14 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, inositol also finds application for the synthesis of inositol nitrate, found in explosives and solid rocket propellants, or glucaric acid, a biopolymer precursor [ 20 ]. This results in a world market of 15,000 tons per year and a global market of USD 60 million by 2020 [ 21 ]. It is mainly produced from phytate (inositol hexakisphosphate, IP6), the main phosphorous storage of plants.…”
Section: Industrially Relevant Enzyme Cascades For Api Synthesismentioning
confidence: 99%
“…It is mainly produced from phytate (inositol hexakisphosphate, IP6), the main phosphorous storage of plants. After its extraction, phytate is chemically dephosphorylated, which suffers from various drawbacks such as phosphorous waste, high production costs and difficult myo -inositol separation [ 21 ]. An alternative route is a cell-based production by metabolically engineered microorganisms such as Escherichia coli with a titer of 106.3 g L −1 (590.5 mM) and a yield of 0.82 mol mol −1 glucose in 23 h [ 51 ].…”
Section: Industrially Relevant Enzyme Cascades For Api Synthesismentioning
confidence: 99%
“…Therefore, in the co-cultivation process of recombinant strains, it was obvious that the metabolic reactions of B. subtilis were drastically altered, including multiple pathways, while the biochemical process of E. coli was relatively simple. Furthermore, in the co-culture system, B. subtilis and E. coli needed to enhance stress tolerance to balance the cells to reduce damage in response to environmental stress, and changing the lipid composition of cell components to regulate membrane fluidity may be a For example, myo-inositol is a precursor substance of many compounds, a type of inositol derivative formed after lipid-dependent phosphorylation, which is both an important membrane structure and signal substance (Li et al 2021). In this study, the upregulation of myoinositol abundance in the co-culture system provides more precursors for lipid synthesis to achieve a cellular stress response.…”
Section: Metabolic Network Analysismentioning
confidence: 99%